The use of autogenous teeth for alveolar ridge preservation : a literature review - Cenicante, João Pedro Alves Valadas de Lima (2021)
Following a tooth extraction, a cascade of biological events will lead inevitably to a decrease in the height and width of the alveolar ridge, mostly on the buccal side and horizontally. In this sense, given how often this procedure is performed in dental practice, it is pivotal that every clinician is acquainted with these dimensional changes and its possible impact on future oral rehabilitation. Consequently, several treatment modalities, commonly known as Alveolar Ridge Preservation (ARP) are described in the literature and include: socket grafting, with the use of a bone graft material, guided tissue regeneration (GTR), with the use of a barrier membrane and finally guided bone regeneration (GBR) with the use both a bone graft material and a barrier membrane. Currently, there are several options for bone graft materials available to the clinician, comprising autografts, allografts, xenografts and alloplasts, having each its advantages and drawbacks. The biological plausibility regarding the use of these biomaterials is that thanks to biological properties intrinsic to the grafts, the alveolar ridge resorption would decrease. In the past decade, the use of autogenous teeth as a bone graft material has been described with encouraging results, nevertheless, describing distinct preparation protocols prior to the ARP procedure. Therefore, this literature review aims to summarize all the evidence regarding the use of autogenous teeth as a bone graft material in ARP in post-extraction sockets, its several preparation protocols, efficacy and future perspectives.